Senescent mesenchymal stem/stromal cells in pre-metastatic bone marrow of untreated advanced breast cancer patients - Borzone, Francisco Raúl (2023)
Breast cancer is the predominant form of carcinoma among women worldwide, with 70% of advanced patients developing bone metastases, with a high mortality rate. In this sense, the bone marrow (BM) mesenchymal stem/stromal cells (MSCs) are critical for BM/bone homeostasis, and failures in their functionality, transform the BM into a pre-metastatic niche (PMN). We previously found that BM-MSCs from advanced breast cancer patients (BCPs, infiltrative ductal carcinoma, stage III-B) have an abnormal profile. This work aims to study some of the metabolic and molecular mechanisms underlying MSCs shift from a normal to an abnormal profile in this group of patients. A comparative analysis was undertaken, which included self-renewal capacity, morphology, proliferation capacity, cell cycle, reactive oxygen species (ROS) levels, and senescence-associated β‑galactosidase (SA‑β‑gal) staining of BM-derived MSCs isolated from 14 BCPs and 9 healthy volunteers (HVs). Additionally, the expression and activity of the telomerase subunit TERT, as well as telomere length, were measured. Expression levels of pluripotency, osteogenic, and osteoclastogenic genes (OCT-4, SOX-2, M-CAM, RUNX-2, BMP-2, CCL-2, M-CSF, and IL-6) were also determined. The results showed that MSCs from BCPs had reduced ,self-renewal and proliferation capacity. These cells also exhibited inhibited cell cycle progression and phenotypic changes, such as an enlarged and flattened appearance. Additionally, there was an increase in ROS and senescence levels and a decrease in the functional capacity of TERT to preserve telomere length. We also found an increase in pro-inflammatory/pro-osteoclastogenic gene expression and a decrease in pluripotency gene expression. We conclude that these changes could be responsible for the abnormal functional profile that MSCs show in this group of patients.